Temporal transcriptional response to ethylene gas drives growth hormone cross-regulation in Arabidopsis - Katherine Noelani Chang; Shan Zhong; Matthew T Weirauch; Gary Hon; Mattia Pelizzola; Hai Li; Shao-shan Carol Huang; Robert J Schmitz; Mark A Urich; Dwight Kuo; Joseph R Nery; Hong Qiao; et al. (eLife, 2013)
The gaseous plant hormone ethylene regulates a multitude of growth and developmental processes. How the numerous growth control pathways are coordinated by the ethylene transcriptional response remains elusive. We characterized the dynamic ethylene transcriptional response by identifying targets of the master regulator of the ethylene signaling pathway, ETHYLENE INSENSITIVE3 (EIN3), using chromatin immunoprecipitation sequencing and transcript sequencing during a timecourse of ethylene treatment. Ethylene-induced transcription occurs in temporal waves regulated by EIN3, suggesting distinct layers of transcriptional control. EIN3 binding was found to modulate a multitude of downstream transcriptional cascades, including a major feedback regulatory circuitry of the ethylene signaling pathway, as well as integrating numerous connections between most of the hormone mediated growth response pathways. These findings provide direct evidence linking each of the major plant growth and development networks in novel ways.